2019
DOI: 10.1101/757088
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The schizophrenia risk locus in SLC39A8 alters brain metal transport and plasma glycosylation

Abstract: A common missense variant (rs13107325 (C->T), A391T) in SLC39A8, a gene encoding a transporter of divalent cations including manganese (Mn), is convincingly associated with schizophrenia and has pleiotropic effects on several additional brain-related phenotypes.Homozygous loss-of-function mutations in SLC39A8 result in undetectable serum Mn and a Congenital Disorder of Glycosylation (CDG) due to the exquisite sensitivity of glycosyltransferases to Mn concentration. Here, we identified Mn-related changes in hum… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 71 publications
2
20
0
Order By: Relevance
“… 9 , 40 The LIF score is no longer used since the medical and MRI physics community is more familiar with T1 for the assessment of inflammation and fibrosis across all specialties including cardiology and neurology. 11 , 18 , [41] , [42] , [43] , [44] , [45] In this GWAS study, the cT1 values reported are standardised across the MRI scanner model and field strength, showing very high repeatability and reproducibility. 46 …”
Section: Discussionmentioning
confidence: 78%
“… 9 , 40 The LIF score is no longer used since the medical and MRI physics community is more familiar with T1 for the assessment of inflammation and fibrosis across all specialties including cardiology and neurology. 11 , 18 , [41] , [42] , [43] , [44] , [45] In this GWAS study, the cT1 values reported are standardised across the MRI scanner model and field strength, showing very high repeatability and reproducibility. 46 …”
Section: Discussionmentioning
confidence: 78%
“…We speculate that alterations in SLC9A9 function might affect sialylation of bisected (addition of bisected GlcNAc) glycans via modulation of Golgi pH. Interestingly, strong defects in another solute carrier, a manganese transporter SLC38A9 (Mn 2+ cations are important cofactors for normal Golgi functioning (Breton et al 2006)), lead to a congenital disorder of glycosylation (Park et al 2015), while the common missense variant rs13107325 in this gene was found to be associated with weak changes in the plasma protein N-glycome (Mealer et al 2019). In Sharapov et al (Sharapov et al 2019), rs13107325 was associated with the percentage of trisialylated structures, although this association did not reach genome-wide significance (nominal P = 6×10 -5 ).…”
Section: Resultsmentioning
confidence: 96%
“…Groups included (a) controls (33 healthy adults homozygous for the major allele (C) at rs13107325 of SLC39A8), (b) parents of P1 and P2 who are heterozygous mutations carriers, and (c) patients P1, P2 as well as two previously described cases of SLC39A8-CDG also analyzed by MALDI-TOF by our group. 19 Experimental analyses were performed at least in duplicates and results are presented as mean with SEM. Statistical analyses were performed on GraphPad Prism Version 8.0 (GraphPad Software, San Diego, California).…”
Section: Discussionmentioning
confidence: 99%
“…We recently published the first MALDI-TOF MS N-glycome profiles of two SLC39A8-CDG cases who also had abnormal transferrin IEF, identifying glycosylation abnormalities that were reversed after a year of manganese supplementation. 19 Here, we describe two patients who show no detectable abnormalities as assessed by conventional glycosylation analysis. By contrast, we identified changes in the serum N-glycome profiling by MALDI-TOF consistent with our prior studies on SLC39A8-CDG.…”
Section: Synopsismentioning
confidence: 97%